DETERMINAN INTENSI KEWIRAUSAHAAN PADA ANGGOTA LEMBAGA KEUANGAN MIKRO PEKERJA INDUSTRI KERAJINAN RAJAPOLAH - Kurniawan, Andri; Winandi, Ratna; Daryanto, Heny K. S. (Jurnal Agribisnis Indonesia, 2013)
Woven pandanus handicraft industry in Rajapolah experience performance degradation as the global crisis in 2008. One of the participating private institutions to develop industry is Microfinance Institutions Koperasi Sejahtera Bangsaku (KSB), which as a medium to understdan the entrepreneurial intentions craft workers in unfavorable economic conditions. This study aims to determine the factors that influence an individuals decision to engage in entrepreneurial activity. The sample was 115 craft industry workers as well as members of the KSB. The data were processed using Partial Least Square analysis (PLS). By using a framework approach to entrepreneurial intentions models, this study found that entrepreneurial intentions is influenced by personal attitude and perceived behavioural control.Â  As nomological of the hypothesized causal paths, external and internal factor that influence entreprenurial intentions are demography, perceived need for new job, entrepreneurship skill, microfinance instituiton, and environmental factor.